An Implementing the Hangman Game in Teaching English Vocabulary to Elementary School Students - Weda Dharmayasa, I Nyoman (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Vocabulary is an important part of language, but in fact, students find it difficult in understanding the vocabulary, especially the fifth-grade students. The Hangman game might inspire pupils to study harder and focus more on the lessons being taught. The objective of the research was to analyze the significant effect of the use of the Hangman game as the media to teaching English vocabulary to fifth-grade students. The method of this research was pre-experimental research with one group and the data were collected through the pre-test and the post-test design. The researcher analyzed the data by using SPSS 26.0 version. The result of the study showed a significant increase in vocabulary mastery of the students. The mean score of the pre-test was 32.89 meanwhile the pre-test score was 81.84. Then the improvement of the students' vocabulary was 48,95%. Which means the post-test score mean score was greater than the pre-test mean score. The paired t-test result was able to be concluded that the value of Sig. (2-tailed) is 0.000 indicates that the t-value was lower than the significant alpha (α = 0.05), the null hypothesis (Ho) was rejected. Meanwhile, the alternative hypothesis (Ha) was accepted. Based on the research findings, it able to be concluded that the Hangman game was effective in teaching students’ vocabulary to the fifth-grade students.